Pterygium Excision with Conjunctival Autograft without Suture and Glue in Rural India (Ukrainian Journal of Ophthalmology, 2025)
Purpose: To determine the rate of complications and surgical outcome of using the sutureless, glueless technique for conjunctival autograft placement in cases of primary pterygium.Material and Methods: A prospective interventional study was conducted in 40 eyes of 40 patients with primary nasal pterygium with grades 2-4 who presented to the ophthalmology Outpatient Department at Chikkballapur Institute of Medical Sciences at Chikkaballapur were enrolled for the study. The patients who needed surgical excision were considered for the study after obtaining informed consent as per the declaration of Helsinki. Visual Acuity was recorded using Snellen's chart. Demographic data, clinical presentations, management, and complications were noted. Data were analysed using Excel Data Analysis Tool and Jamovi 2.3.20 statistical analysis tool.Results: A total of 40 patients were included in the study. The mean age group was 48.1 years (the minimum being 28 and the maximum being 70, and pterygium generally prevailed in the age group between 30 and 60 years. Gender selection was not conducted in this study. However, random enrollment indicated that the F:M ratio was 4:1. The recurrence rate was very low, 5% in cases using the glueless, sutureless technique, and the other complications were comparable with other techniques: graft displacement 7.5%, graft missing on the first post operative day in 2.5%, graft wrinkling and shrinkage in 10%, postoperative foreign body sensation and pain in 30%, and photophobia in 15%.Conclusion: This technique proved that the recurrence rate was very low, which is the main aim of pterygium excision. The BCVA was significantly improved after the operation.
Keywords: pterygium excision; sutureless technique; glueless technique; conjunctivalautograft